2023
DOI: 10.1530/joe-22-0271
|View full text |Cite
|
Sign up to set email alerts
|

Immunology of chronic low-grade inflammation: relationship with metabolic function

Abstract: Inflammation is part of the body’s innate immune response and is an essential process that not only defends against harmful bacteria and pathogens but also plays a key role in the maintenance and repair of tissues. Under pathological conditions, there is bilateral crosstalk between immune regulation and aberrant metabolism resulting in persistent inflammation in the absence of infection. This phenomenon is referred to as sterile metabolic inflammation (metainflammation) and occurs if the initiating stimulus is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 78 publications
0
15
0
Order By: Relevance
“…The elevation of proteins in CON indicates a systemic innate immune system activation consistent with higher serum CRP and metabolic in ammation (27)(28)(29)(30)(31). Serum amyloid P (APCS), for example, is a pentraxin and an acute phase protein that along with CRP promotes phagocytosis via complementdependent pathways (32).…”
Section: Discussionmentioning
confidence: 99%
“…The elevation of proteins in CON indicates a systemic innate immune system activation consistent with higher serum CRP and metabolic in ammation (27)(28)(29)(30)(31). Serum amyloid P (APCS), for example, is a pentraxin and an acute phase protein that along with CRP promotes phagocytosis via complementdependent pathways (32).…”
Section: Discussionmentioning
confidence: 99%
“…MetS is a tremendously growing public health problem, which is comprised of interconnected and heterogeneous metabolic origin risk factors that appear to be directly promoting the development of type 2 DM, adverse cardiovascular events and all‐cause mortality 24 . MetS induces low‐grade chronic systemic inflammation in the circulation and peripheral metabolic tissues, defined as ‘metabolic inflammation’, which is different from classical inflammation 25,26 . Numerous studies confirmed that CRP as a conventional marker of systemic inflammation is correlated with the number of MetS components (i.e.…”
Section: Discussionmentioning
confidence: 99%
“… 24 MetS induces low‐grade chronic systemic inflammation in the circulation and peripheral metabolic tissues, defined as ‘metabolic inflammation’, which is different from classical inflammation. 25 , 26 Numerous studies confirmed that CRP as a conventional marker of systemic inflammation is correlated with the number of MetS components (i.e. MetS severity) and a higher CRP level was associated with an increased incidence of cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…Pathological alterations in cell metabolism and abnormal activation of innate immunity associated with excess fatty acids, their transport, accumulation of lipid droplets and disruption of interorganelle connections lead to reprogramming of nuclear DNA: expression of certain transcription factors and genes that activate the processes of cell aging, cell death and maintenance of the inflammatory response. The link between sterile metabolic inflammation in obesity and aging processes at the cellular and organismal level is emphasized ( Lee, 2022 ; van de Vyver, 2023 ). An increase in the number of senescent cells, which differ in genotype and produce a secretory pro-inflammatory phenotype/senescence-associated phenotype (SASP), inhibit adipogenesis and induce the development of insulin resistance (IR) ( Palmer et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%